2015
DOI: 10.1021/acs.iecr.5b02150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyanuric Acid on Crystallization Behavior, Polymorphism, and Phase Transition of Poly(butylene adipate)

Abstract: ABSTACT: Effects of the cyanuric acid (CA) on the isothermal and non-isothermal crystallization, morphology, polymorphic crystalline structure and phase transition on the PBA have been investigated systematically by differential scanning calorimetry (DSC), polarized optical microscopy (POM), wide angle X-ray diffraction (WAXD), Fourier transform infrared (FTIR) spectroscopy. The non-isothermal crystallization temperature increased upon addition of the CA. The crystallization kinetics in the isothermal crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 55 publications
(127 reference statements)
2
27
0
Order By: Relevance
“…In this work, the preferential formation of the PBA α ‐modification (that is, decreased T c, α ) is probably attributed to a good crystal lattice matching (between the PBA α ‐crystal and the EBH crystal) which induces the epitaxial growth of the PBA α ‐crystal on the EBH surface. Several similar results suggest that the polymorphic selective effect of the NA on the PBA α ‐crystal is mainly attributed to the perfect crystal lattice matching . More in‐depth investigation is needed.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In this work, the preferential formation of the PBA α ‐modification (that is, decreased T c, α ) is probably attributed to a good crystal lattice matching (between the PBA α ‐crystal and the EBH crystal) which induces the epitaxial growth of the PBA α ‐crystal on the EBH surface. Several similar results suggest that the polymorphic selective effect of the NA on the PBA α ‐crystal is mainly attributed to the perfect crystal lattice matching . More in‐depth investigation is needed.…”
Section: Resultsmentioning
confidence: 90%
“…Nucleating agents (NAs) have been widely utilized to alter physical properties and improve various performances (mechanical properties, biodegradation, gas barrier, transparency, electrical conductivity, thermal stability, and so on) of polymeric material, due to the efficiency, low cost, convenience and ease of fabrication of the composite material . Some NAs have been used to manipulate the crystallization behavior, polymorphic crystalline structure and biodegradation of PBA . Owing to weak interface bonding strength between PBA and NA (in particular, inorganic NAs) and insolubility of the NA in the melting PBA matrix, agglomeration (that is, inhomogeneous dispersion) of the NA occurs, resulting in a difficulty in controlling the crystal shape/size and enhancing the nucleation ability.…”
Section: Introductionmentioning
confidence: 99%
“…Other, albeit less informative, assignments can be found in the literature, such as Padgett and Hamner, 16 Loughran et al, 17 Chen et al, 18 and Surinwong et al 19 References can also be found in the literature regarding polymorphs of cyanuric acid derivatives, such as Barnett et al, 20 who discuss the polymorphism in hydrogen bonded adducts of cyanuric acid-bis(4-pyridyl)ethane, and Yang et al, 21 who address the effects of cyanuric acid on the polymorphism of poly(butylene adipate).…”
Section: Introductionmentioning
confidence: 99%
“…9 The b crystal can transform to the a crystal by annealing at a relatively high temperature, which has been demonstrated to be a solid-solid transformation process. Therefore, besides temperature, the nucleating agent, [11][12][13][14] blending, 15-20 copolymerization, 10,21,22 substrate, [23][24][25][26] and tension, 9 etc. 10 Polymorphism regulation of PBA is a hot research topic, because both a and b PBA crystals can be easily obtained and stay rather stable under mild conditions compared with other polyesters.…”
Section: Introductionmentioning
confidence: 99%
“…8 Recently, we have shown that the b / a crystal transformation mechanism would change to melt-recrystallization aer randomly introducing butylene fumarate units into PBA main chains. For example, added carbon nanobers can expand the formation temperature of the a crystal to as low as 0 C, 13 and the b / a crystal transformation behavior of PBA in the PBA/poly(vinyl phenol) (PVPh) blends could be signicantly accelerated due to the formation of intermolecular hydrogen bonds and the appearance of imperfect b crystals. Therefore, besides temperature, the nucleating agent, [11][12][13][14] blending, 15-20 copolymerization, 10,21,22 substrate, [23][24][25][26] and tension, 9 etc.…”
Section: Introductionmentioning
confidence: 99%